Loans for vocational education and training in Europe - (:unkn) unknown (Publications Office of the European Union, 2012)
"This Cedefop report examines the design and performance of loans for (vocational) education and training across Europe and provides indepth analysis of the loan schemes in eight selected countries: France, Hungary, the Netherlands, Austria, Poland, Finland, Sweden and the UK. The report is largely based on information collected via surveys of loan scheme managers, experts on financing (vocational) education and training, and other key national stakeholders, as information from secondary sources was relatively scarce. The analysis covers aspects such as types of loan, objectives pursued, access and repayment conditions, management and administration, the role of government, financial institutions and other actors. The performance of loans is assessed according to five evaluation criteria: effectiveness (take-up rates), efficiency (default rates and administrative costs), equity, impact (impact on beneficiaries; deadweight and substitution effects) and sustainability (financial and political). The appraisal relies strongly on the opinions of the survey respondents. The report looks also at the experience of non-EU countries in improving their loan schemes and formulates recommendations for European policy and practice." (Hrsg., BIBB-Doku)
Keywords: S 4.4 Finanzierungsmodelle; I 2.2 Europa; Bildungsfinanzierung; Darlehen; Kreditwesen; Wirkungsforschung; Internationaler Vergleich; Europa